Involvement of different protein kinases and phospholipases A2 in phorbol ester (TPA)-induced arachidonic acid liberation in bovine platelets - M. Lehr; K. Griessbach (Mediators of Inflammation)
The effect of various phospholipase A2 and protein kinase inhibitors on the arachidonic acid liberation in bovine platelets induced by the protein kinase activator 12-O-tetradecanoylphorbol–13-acetate (TPA) was studied. TPA stimulates arachidonic acid release mainly by activating group IV cytosolic PLA2 (cPLA2), since inhibitors of this enzyme markedly inhibited arachidonic acid formation. However, group VI Ca2+-independent PLA2 (iPLA2) seems to contribute to the arachidonic acid liberation too, since the relatively specific iPLA2 inhibitor bromoenol lactone (BEL) decreased arachidonic acid generation in part. The pronounced inhibition of the TPA-induced arachidonic acid release by the protein kinase C (PKC) inhibitors GF 109203X and Ro 31–82220, respectively, and by the p38 MAP kinase inhibitor SB 202190 suggests that the activation of the PLA2s by TPA is mediated via PKC and p38 MAP kinase.